MIS 5/4 transition in a mountain environment: herpetofaunal assemblages from Cueva del Camino, central Spain. (16th May 2013) - Blain, Hugues‐Alexandre; Laplana, César; Sevilla, Paloma; Arsuaga, Juan Luis; Baquedano, Enrique; Pérez‐González, Alfredo
<x xml:space="preserve">Abstract</x> The Cueva del Camino site (Pinilla del Valle, Madrid, Spain) is located in the upper valley of the Lozoya River in the Sierra de Guadarrama, a mountain range extending NE−SW within the Central Range System. Due to its location within a mountain range on the central Iberian Peninsula at an altitude of 1114 m a.s.l. and the numerical dating of its sediments, the palaeontological site of Cueva del Camino has proved a highly relevant location for studying the ecological changes linked to the climatic fluctuations at the end of Marine Isotope Stage (MIS) 5 and the beginning of MIS 4. Environmental reconstructions suggest a rather open, patchy landscape throughout the succession, with abundant evidence of dry meadows, scrublands and rocky habitats. The climate can be considered as generally warm, reaching mean annual temperatures (MATs) of up to 13.8°C (i.e. higher than today's by up to 2.9°C). Three cooler events can be seen throughout the succession as reflected by the presence of Rana iberica, Anguis fragilis and Coronella austriaca. The first of these events may correlate with MIS 5b; the second in the Central sector may correlate with the Stadial I pollen event occurring at the end of MIS 5a; and the third event, corresponding to the coldest MAT of the entire succession with MATs 0.9°C lower than today's, may correspond to the transition from MIS 5a to MIS 4. The evolution of mean annual precipitation (MAP) is characterized by warm periods, drier and cold periods, as well as wetter periods (up to +356 mm compared to today's MAP values), similar to what occurs today in the high‐elevation areas of the neighbouring mountains. Our study gives new quantitative estimations for the climatic fluctuations in mountain environments of central Spain at the MIS 5/4 transition and their associated ecological changes.